(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Pericarditis is inflammation of the pericardium, often with fluid accumulation in the pericardial cavity. Pericarditis can occur for a variety of reasons (e.g., infectious diseases, myocardial infarction, trauma, tumors, metabolic disorders), but is most often idiopathic. Symptoms of pericarditis include chest pain or tightness, often worsened by deep breathing. If cardiac tamponade or constrictive pericarditis develops, cardiac output may be significantly reduced. Diagnosis is based on symptoms, auscultatory findings (pericardial friction rub), electrocardiographic changes, and the presence of fluid accumulation in the pericardial cavity on radiography or echocardiography. Further investigation is required to determine the cause. Treatment depends on the cause, but usually includes analgesics, anti-inflammatory drugs, colchicine, and occasionally surgery.